Issues and Challenges Faced by the Indigenous Students of Tripura in Primary-level to Higher Education: An overview - Tripura, Timothy (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
The objective of the paper is to study the critical issues and challenges faced by the tribal students of Tripura in primary level to higher education from the perspective of their socio-economic status, medium of instructions in school, attitude of parents, teachers and peer groups etc. It will also give an analysis of the status of literacy rate, gross enrolment ratio and gender parity index.The present paper is mostly based on informal interviews (to few students, parents and teachers) and secondary data from various research studies including census data, committee reports on tribal, annual reports of tribal welfare ministry, Government organisations, Report on Selected Educational Statistics etc.Keywords: challenges; issues; Higher education; socio-economic, tribal students.